2016
DOI: 10.1038/srep39294
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cancer risk lncRNAs and cancer risk pathways regulated by cancer risk lncRNAs based on genome sequencing data in human cancers

Abstract: Cancer is a group of diseases involving abnormal cell growth with the potential to invade or spread to other parts of the body. The complexity of cancer can be reduced to a small number of underlying principles like cancer hallmarks which could govern the transformation of normal cells to cancer. Besides, the growth and metastasis of cancer often relate to combined effects of long non-coding RNAs (lncRNAs). Here, we performed comprehensive analysis for lncRNA expression profiles and clinical data of six types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Although there is a rapid increase in the mapping of lncRNA loci, the elucidation of the biological role of novel lncRNAs is still in his infancy. From our literature review, we found that only one prognostic lncRNAs in the LFES, NRAV , has been found to express in numerous human tissues and identified as cancer-related lncRNA in bladder urothelial carcinoma, kidney chromophobe and kidney renal papillary cell carcinoma [ 32 ]. A previous study of NRAV showed that NRAV was dramatically down-regulated during infection with several viruses and was indicated as a critical regulator of innate immunity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a rapid increase in the mapping of lncRNA loci, the elucidation of the biological role of novel lncRNAs is still in his infancy. From our literature review, we found that only one prognostic lncRNAs in the LFES, NRAV , has been found to express in numerous human tissues and identified as cancer-related lncRNA in bladder urothelial carcinoma, kidney chromophobe and kidney renal papillary cell carcinoma [ 32 ]. A previous study of NRAV showed that NRAV was dramatically down-regulated during infection with several viruses and was indicated as a critical regulator of innate immunity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 2% of human genome is protein-coding genes while 98% is non-coding genes [4], among which, those with at least 200 nucleotides in length are defined as long non-coding RNAs (lncRNAs) [5]. Increasing evidence has proved lncRNAs play a rather crucial role in pathophysiological process including tumorigenesis [6][7][8][9][10]. LncRNAs regulate biological behaviors including cell proliferation, cell apoptosis, cell metastasis etc., during tumorigenesis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“… 4 Previous studies have confirmed that lncRNAs play critical roles in tumorigenesis and cancer development. 5 Moreover, lncRNAs are detectable and relatively stable in cell-free body fluids, indicating great potential of circulating lncRNAs for biomarker applications. 6 In one study, for example, lncRNA H19 expression was upregulated in plasma samples from patients with gastric cancer and significantly associated with the TNM stage.…”
Section: Introductionmentioning
confidence: 99%